2014
DOI: 10.1111/ijcp.12492
|View full text |Cite
|
Sign up to set email alerts
|

The use of robotics in surgery: a review

Abstract: Robotic surgery has been shown to shorten hospital stays, decrease complication rates and allow surgeons to perform finer tasks, when compared to the traditional laparoscopic and open approaches. These benefits, however, must be balanced against increased intraoperative times, vast financial costs and the increased training burden associated with robotic techniques. The outcome of such a cost-benefit analysis appears to vary depending on the procedure being conducted; indeed the strongest evidence in favour of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
69
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 56 publications
0
69
0
8
Order By: Relevance
“…The robot was first introduced to the surgical arena in the 1980s in the form of telesurgery [1]. Through several modifications and advancements since then, robotic surgery has established itself as a valid option for patients undergoing certain surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The robot was first introduced to the surgical arena in the 1980s in the form of telesurgery [1]. Through several modifications and advancements since then, robotic surgery has established itself as a valid option for patients undergoing certain surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, RCS may offer an advantage in dissection in the deep pelvis especially in patients who have undergone pre-operative chemotherapy [2,9]. While each surgical method offers some advantages over the other, several studies have demonstrated comparable outcomes between robotic and laparoscopic colorectal surgery for intra-operative morbidity, complication rates, and postoperative recovery [1,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…So far, patient benefits of robotic-assisted (DaVinci) surgery have been shown in urology, especially for prostatectomy [3]. Benefits for surgeons in the area of ergonomic operations have recently been more and more the focus of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Robot-guided interventions (RGI) are used to accurately position or to navigate surgical instruments to specific targets planned by using medical images [1]. Medical images are derived using imaging technologies of computed tomography (CT), magnetic resonance imaging (MRI) or ultrasound; they are used to provide an insight into the interior of a human body.…”
Section: Introductionmentioning
confidence: 99%